2017
DOI: 10.1016/j.optom.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of neuropathic mechanisms in dry eye syndromes

Abstract: Dry eye syndromes can involve both nociceptive and neuropathic symptoms. Nociceptive symptoms are the normal physiological responses to noxious stimuli. Neuropathic symptoms are caused by a lesion or disease of the somatosensory nervous system and can be the result of hypersensitisation of peripheral or central corneal and conjunctival somatosensory nerves. For example, inflammation could induce neuroplastic peripheral sensitisation of the ocular surface or lid wiper and exacerbate nociceptive symptoms. Neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 59 publications
(125 reference statements)
1
62
0
3
Order By: Relevance
“…Recently, the concept of neuropathic pain has emerged as an important factor for dry eye development, and hypersensitivity to the unstable tear film is considered the mechanism underlying dry eye. [30][31][32][33][34][35] Kaido et al 14 reported in 2016 that hypersensitivity of the cornea exists in short TBUT-type dry eye, speculating that the severe symptoms of short TBUT-type dry eye may be due to the neuropathic pain components.…”
Section: History Of the Short Tbut-type Dry Eyementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the concept of neuropathic pain has emerged as an important factor for dry eye development, and hypersensitivity to the unstable tear film is considered the mechanism underlying dry eye. [30][31][32][33][34][35] Kaido et al 14 reported in 2016 that hypersensitivity of the cornea exists in short TBUT-type dry eye, speculating that the severe symptoms of short TBUT-type dry eye may be due to the neuropathic pain components.…”
Section: History Of the Short Tbut-type Dry Eyementioning
confidence: 99%
“…58 Galor et al and other groups are exploring multiple treatment approaches in this field, and new developments are expected in the near future. [31][32][33][34][35]…”
Section: Treatment Of Short Tbut-type Dry Eyementioning
confidence: 99%
“…[107][108][109][110][111] Furthermore, DED often develops in glaucoma patients, since glaucoma medication is toxic to the ocular surface. 112 Secondly, it is highly likely that pain [113][114][115] in patients with DED may be associated with sleep disorders. Sleep disorders with pain have been suggested in pSS and other rheumatic diseases.…”
Section: Possible Explanation For Sleep Disorders In Dedmentioning
confidence: 99%
“…For neuropathic pain, considering that pain can become spontaneous and unresponsive to artificial tear instillation once central sensitization develops, limitation of the neuroplastic sensitization process by prevention of ocular surface damage and inflammation in the initial stages would be important 2,21,56,82. Aggressive treatment with anti-inflammatory medications is necessary for relief of acute pain and improvement of ocular surface inflammation 56,82.…”
Section: Managementmentioning
confidence: 99%
“…Although this discrepancy can partly be explained by the limited reliability of the dry eye tests currently available; individual differences in cognitive response to dry eye questionnaires,9 the heterogeneous nature of DED and individual variability in the perception of dry eye symptoms may also play an important role 9. In particular, studies focused on the association of DED with neurological or psychiatric disorders have suggested the role of neurological or psychological factors in the development of dry eye symptoms, particularly in elderly patients 2,12,1721. Vehof et al17 recently showed that severe dry eye symptoms unproportional to external signs were associated with lower level of self-perceived health.…”
Section: Introductionmentioning
confidence: 99%